Ullmann coupling reactions on Ag(111) and Ag(110); substrate influence on the formation of covalently coupled products and intermediate metal-organic structures Metal-Organic Structures - Judd, Chris J.; Haddow, Sarah Louise; Champness, Neil R.; Saywell, Alexander (Nature Publishing Group, 2017)
On-surface reactions based on Ullmann coupling are known to proceed on coinage-metal substrates (e.g. Au, Ag, Cu), with the chemistry of the surface strongly influencing the reaction progression. In addition, the topography of the surface may be expected to affect the local adsorption geometry of the reactants as well as the intermediate and final structures. Here, we investigate the effect of two different surface facets of silver, Ag(111) and Ag(110) on the formation of organometallic and covalent structures for Ullmann-type coupling reactions. Deposition of 4,4”-diiodo-m-terphenyl molecules onto either Ag(111) or Ag(110) surfaces leads to the scission of C-I bonds followed by the formation of organometalic zigzag structures, consisting of molecules connected by coordination bonds to Ag adatoms. The covalently coupled product is formed by annealing each surface, leading to the removal of Ag atoms and the formation of covalently bonded zigzag poly(m-phenylene) structures. Comparisons of the adsorption model of molecules on each surface before and after annealing reveal that on Ag(111), structures rearrange by rotation and elongation of bonds in order to become commensurate with the surface, whereas for the Ag(110) surface, the similarity in adsorption geometry of the intermediate and final states means that no rotation is required.